Lafede nel Figlio di Dio prima di Nicea: teologia del Logos e prospettive contemporanee a confronto. - Cristaudo, Alfio Giovanni 1983- (2025)
The consolidation of the Nicene faith, in the strong opposition to Arianism, led to the definitive dismissal of the previous "Trinitarian" models, characterized by an accentuated subordinationism, in the fear that these paradigms could call into question the full divinity of the Son and his equality with the Father. One of these doctrines is that of the "two stages" of the Logos. This article, after having illustrated the characteristics of the ancient pre-Nicene paradigm, shows some of the advantages connected to its adequate recovery, underlining the analogies with some instances of contemporary theological reflection.